Evaluation of salivary nitric oxide level in children with early childhood caries - A R Senthil Eagappan; V Arun Prasad Rao; S Sujatha; D Senthil; J Sathiyajeeva; G Rajaraman (Wolters Kluwer Medknow Publications, 2016)
Background: Nitric oxide (NO), a highly reactive radical, participates in the nonspecific natural defense mechanism of the oral cavity. The present study was attempted to evaluate the salivary NO levels in 4-5 year-old children with early childhood caries (ECC). The objective of the present study was to assess the salivary NO concentration in children with different caries activity. Materials and Methods: The study included 120 healthy 4-5 year-old children and they were equally divided into three groups based on decayed, missing, filled surfaces (dmfs) score; forty caries-free children (control group), forty children with dmfs 1-5 (ECC group), and forty with dmfs ≥6 (severe ECC group). Saliva collected was measured for NO concentration by Griess reaction method. The obtained data were analyzed by ANOVA and Pearson's correlation coefficient. Results: The mean level of NO in the saliva of the control group was 51.2 ± 8.3457 and that of ECC and severe ECC were 47.1 ± 5.2614 and 33.625 ± 4.6942, respectively. The mean salivary NO concentration was significantly higher in healthy controls when compared to children with ECC and severe ECC. Moreover, a negative correlation (r = −0.6658) was observed between the salivary NO level and the mean dmfs, suggesting that as the salivary NO level decreases, the caries incidence increases. Conclusion: The obtained results support the antimicrobial activity of salivary NO and also suggest that an increase in NO production might contribute to lower the caries occurrence in children.